Kashmir Peasant Economy under Dogra’s: A Case Study of Agrarian Produce and Livestock 1885-1925 A.D - Bhat, Jamsheed; Khanday, S.A (Journal of Social Economics Research, 2014)
Just as the Indian economy which is mainly agrarian based, the economy of the princely state of Jammu & Kashmir was/is primarily agricultural. The bulk of the people in the state lived on agriculture. Agriculture therefore, constituted the backbone of the Kashmir’s economy and prosperity of the state depends upon the well-being of its peasant. The socio-economic life in Kashmir has always been very deeply rooted in agrarian sector, the peasant’s main domain. The present study entitled “Kashmir Peasant Economy under Dogra’s: A Case study of Agrarian produce and Livestock 1885-1925 A.D.”, is a humble yet sincere attempt by the researcher to critically examine the agricultural produce and livestock of peasant economy and to assess the validity of the statement of ‘the dawn of modernism’. The Third study is devoted for assessment of the peasant economy in the light of rural produce and livestock. It elaborates on a wide variety of crops (both Kharif and Rabi) cultivated by Kashmiri peasant. Furthermore makes it clear how the nature of agrarian produce, the productivity of land and yield per acre was significantly controlled and determined by the regimes, and also discusses the role of animal husbandry, the backbone of rural economy. The study is based on sources both conventional and non-conventional. A good use of primary sources like archival material, contemporary work biographies, travel accounts, poetic literature have been made use of for putting the history of this period into proper perspective and to formulate the conceptual framework for this study.